2002
DOI: 10.1002/pros.10171
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the estrogen receptor beta (ERβ) in human prostate tissue, premalignant changes, and in primary, metastatic, and recurrent prostatic adenocarcinoma

Abstract: The secretory epithelium is a major target of ERbeta-mediated estrogen signaling in the human prostate. Its downregulation in HGPIN is consistent with chemopreventive effects that the ERbeta may exert on the prostatic epithelium. The continuous expression of the receptor protein at significant levels in untreated primary and metastatic adenocarcinoma indicates that these tumors can use estrogens through an ERbeta-mediated pathway. The partial loss of the ERbeta in recurrent tumors after androgen-deprivation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
175
0
18

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(199 citation statements)
references
References 22 publications
6
175
0
18
Order By: Relevance
“…Recently, various studies have shown decreased expression of ERb mRNA and protein (or an increased ERa/ERb mRNA ratio) in cancer vs normal tissues in many tumors, including breast, ovary, colon, and prostate (Foley et al 2000, Campbell-Thompson et al 2001, Roger et al 2001, Fixemer et al 2003, Bardin et al 2004. Moreover, ERb gene is localized on chromosome 14q (see Ascenzi et al 2006 and references therein), the loss of which has been detected in breast, ovarian, prostate, and colon cancers (Young et al 1993, Bandera et al 1997, Loveday et al 2000, Kasahara et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various studies have shown decreased expression of ERb mRNA and protein (or an increased ERa/ERb mRNA ratio) in cancer vs normal tissues in many tumors, including breast, ovary, colon, and prostate (Foley et al 2000, Campbell-Thompson et al 2001, Roger et al 2001, Fixemer et al 2003, Bardin et al 2004. Moreover, ERb gene is localized on chromosome 14q (see Ascenzi et al 2006 and references therein), the loss of which has been detected in breast, ovarian, prostate, and colon cancers (Young et al 1993, Bandera et al 1997, Loveday et al 2000, Kasahara et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Accordingly, there have been several studies describing that a loss of ERb expression is seen in high-grade prostate intraepithelial neoplasia and high-grade dysplasia compared with normal prostate epithelium expressing ERb. [23][24][25] Recent experimental studies have demonstrated that ERb behaves as a tumor suppressor gene. Hurtado et al 26 for example showed that overexpression of ERb1 (ERb) induced a cell cycle arrest in the early G1 phase in LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results have been reported regarding the frequency of the ERb expression and its correlation to the grade in prostate cancer. 24,25,28,29 With regard to ERa, recent investigations have emphasized the important role of ERa in prostatic carcinogenesis. 30,31 Although those studies seem to illustrate the role of ERs in the prostatic gland, an issue still remains whether the endogenous ERs will actually be activated by their ligands followed by the ER-mediated induction of the relevant genes.…”
Section: Discussionmentioning
confidence: 99%
“…Embora Harvey et al, tenham demonstrado que pacientes apresentando 1% ou mais das células tumorais de carcinoma de mama expressando receptor de estrogênio, em intensidade moderada ou forte, responderam positivamente a terapia hormonal (Harvey et al;, existe também uma variação na interpretação do escore inicial da marcação do receptor de estrogênio, variando de 1% a 10%, considerando ou não a intensidade (Hammond et al, 2010). De acordo com as recomendações de Hammond et al (2010) A presença e quantidade das duas isoformas dos receptores de estrogênio é, atualmente, mais estudada em câncer de mama, ovário, cólon e próstata (Fixemer et al, 2003, Bardini et al, 2004Carruba, 2007 (Roger et al, 2001) e em próstata (Carruba, 2007). Bardini et al No entanto, no presente estudo verificou-se maior expressão de REβ e pouca presença de Reα, ou seja, uma relação Reα/ REβ diminuída, situação oposta daquelas observadas nas neoplasias de mama, ovário, cólon e próstata (Skrlis et al 2003, Roger et al, 2001¸Carruba, 2007.…”
Section: Discussionunclassified
“…Acredita-se que o desequilíbrio entre a quantidade de receptores alfa e beta nos órgãos reprodutivos possa estar relacionada ao surgimento de neoplasias (Fixemer et al, 2003, Bardini et al, 2004, Carruba, 2007.…”
Section: Hormônios: Androgênio E Estrogênio: Seus Receptores E a Enziunclassified